Dehydrogenative Meyer–Schuster‐Like Rearrangement: A Gold‐Catalyzed Reaction Generating an Alkyne1. Issue 4 (11th December 2013) - Yu, Yang; Yang, Weibo; Pflästerer, Daniel; Hashmi, A. Stephen K.
Abstract Easily accessible propargylic esters are converted to the inverted alkynyl ketones in an oxidative gold‐catalyzed reaction. Gagosz's catalyst in combination with PhI(OAc)2 is the best system for this conversion and 18 examples with yields up to 80 % are reported. The results indicate that the triple bond in the product is formed by elimination from a vinylgold intermediate. In a formal sense the new conversion overall is a dehydrogenative Meyer–Schuster rearrangement.